Targeting the Full Length of the Motor End Plate Regions in the Mouse Forelimb Increases the Uptake of Fluoro-Gold into Corresponding Spinal Cord Motor Neurons - Tosolini, Andrew P.; Mohan, Rahul; Morris, Renée (Frontiers in Neurology, 2013)
Lower motor neuron dysfunction is one of the most debilitating motor conditions. In this regard, transgenic mouse models of various lower motor neuron dysfunctions provide insight into the mechanisms underlying these pathologies and can also aid the development of new therapies. Viral-mediated gene therapy can take advantage of the muscle-motor neuron topographical relationship to shuttle therapeutic genes into specific populations of motor neurons in these mouse models. In this context, motor end plates (MEPs) are highly specialised regions on the skeletal musculature that offer direct access to the pre-synaptic nerve terminals, henceforth to the spinal cord motor neurons. The aim of this study was two-folded. First it was to characterise the exact position of the MEP regions for several muscles of the mouse forelimb using acetylcholinesterase histochemistry. This MEP-muscle map was then used to guide a series of intramuscular injections of Fluoro-Gold (FG) in order to characterise the distribution of the innervating motor neurons. This analysis revealed that the MEPs are typically organised in an orthogonal fashion across the muscle fibres and extending throughout the full width of each muscle. Furthermore, targeting the full length of the MEP regions gave rise to a seemingly greater number of labelled motor neurons that are organised into columns spanning through more spinal cord segments than previously reported. The present analysis suggests that targeting the full width of the muscles’ MEP regions with FG increases the somatic availability of the tracer. This process ensures a greater uptake of the tracer by the pre-synaptic nerve terminals, hence maximising the labelling in spinal cord motor neurons. This investigation should have positive implications for future studies involving the somatic delivery of therapeutic genes into motor neurons for the treatment of various motor dysfunctions.